Eighteenth-century characters a guide to the literature of the age - McGirr, Elaine M. 1972- (Palgrave Macmillan, 2007)
Eighteenth-Century Characters offers a concise introduction to the eighteenth century, using characters as its starting point. Elaine M. McGirr presents contextualized readings of stock characters from canonical and popular literature, such as: - the rake and the fop - the country gentleman - the good woman - the coquette and the prude - the country maid and the town lady - the Catholic, the Protestant and the British Other. Each chapter explores how a character's significance and role changes over the century, illustrating and explaining radical shifts in taste, ideology and style. Also featuring illustrations, a Chronology and a helpful Bibliography and Further Reading section, this essential guide will provide students with the necessary background to understand the period's literature and to embark on further study.
Includes bibliographical references and index
Keywords: Geschichte 1700-1800; Caractérologie - Dans la littérature; Littérature anglaise - 18e siècle; English literature -- 18th century -- History and criticism; Characters and characteristics in literature; National characteristics, English, in literature; Charakterisierung; Englisch; Nationalcharakter -- Motiv; Literatur